[Distribution of intestinal parasites detected in the Tokat public health laboratory during the period from January 2007 - December 2009]. [Tokat Halk Sa?li?i Laboratuvarinda Ocak 2007-Aralik 2009 Yillari Arasinda Saptanan Ba?irsak Parazitlerinin Dağılımı] - Ataş, A. D.; Kuşcuoğlu, S. (My University, 2010)
In this study, the results of 1868 stool samples and 215 cellophane tapes examined in the Tokat Public Health Laboratory between January 2007-December 2009 and the distribution of these parasites were evaluated retrospectively. A total of 1868 stool specimens from 1146 (61.3%) males and 722 (38.7%) females were examined for intestinal parasites using direct examination and the formol-ethyl acetate concentration methods. Intestinal parasites were found in 40 (2.1%) females and 85 (4.6%) males. A total of 215 cellophane tape specimens from 86 (40%) females and 129 (60%) males were examined. Parasites were detected in 6 (2.8%) female and 11 (5.1%) male patients. The distribution of intestinal parasites detected in stool specimens was as follows: 52 (2.8%) Giardia intestinalis, 15 (0.8%) Entamoeba histolytica/dispar, 46 (2.5%) Entamoeba coli, 2 (0.1%) Hymenolepis nana, 16 (0.9%) Taenia saginata, 3 (0.2%) Ascaris lumbricoides, and 1 (0.05%) Trichuris trichiura. Parasites detected in cellophane tape specimens included 17 (7.9%) Enterobius vermicularis and 3 (1.4%) Taenia saginata. Despite being labor-intensive, parasitological examination of stool samples with necessary staining methods by experienced staff will surely help to determine both the diagnosis and exact prevalence of intestinal parasitic infections in Turkey.
PubMed ID: 20954116